2016
DOI: 10.1186/s13613-016-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome is associated with less negative fluid balance in patients with aneurysmal subarachnoid hemorrhage treated with prophylactic vasopressor-induced hypertension

Abstract: BackgroundAneurysmal subarachnoid hemorrhage (SAH) is a serious condition associated with high mortality rates and long-term disability. We investigated the impact of fluid balance on neurologic outcome after adjustment for possible confounders related to intensive care therapy and extra-cerebral organ failure during the early phase after SAH.MethodsIn this retrospective study, we analyzed data from all 142 adult patients admitted to our university hospital surgical intensive care unit (ICU) with SAH between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…An analysis of the vasopressin and septic shock trial [ 3 ] also showed that a more positive FB at 12 hours and cumulatively over 4 days is associated with increased risk of mortality. Similar results were also reported in other specific patient populations, such as those with acute renal failure [ 4 ], acute lung injury [ 5 ], aneurysmal subarachnoid hemorrhage (ASH) [ 6 ] and surgical patients [ 7 ].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…An analysis of the vasopressin and septic shock trial [ 3 ] also showed that a more positive FB at 12 hours and cumulatively over 4 days is associated with increased risk of mortality. Similar results were also reported in other specific patient populations, such as those with acute renal failure [ 4 ], acute lung injury [ 5 ], aneurysmal subarachnoid hemorrhage (ASH) [ 6 ] and surgical patients [ 7 ].…”
Section: Introductionsupporting
confidence: 80%
“…Sakr et al [6] reported that a more negative FB (up to 7 days) is associated with better outcomes in patients with ASH (–0.7 L vs. –5.6 L, p  < 0.001). However, this comparison between a slight and a more negative FB may have been influenced by the inclusion of patients with positive FB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is some evidence suggesting a beneficial physiologic effect on cerebral perfusion, 9 the various components were each the subject of dispute over the last several years. 10-12 The first effective medical intervention for the prevention of DCI was oral nimodipine, which was shown to reduce the rate of DCI and improve functional outcome. 13 , 14 …”
mentioning
confidence: 99%
“…Remarkably, comparable findings were reported in other studies, primarily focusing on non-ischemic cerebral injuries as for instance subarachnoid hemorrhage (SAH). In detail, three studies have reported the association between a greater cumulative fluid balance within the first days after the bleeding event and an elevated risk of poor outcome (2325). Also in a time frame beyond the first days after SAH, which represents the subacute and thus critical period for the generation of vasospasm, the induction of a positive fluid balance was found to be associated with a poor functional outcome (20).…”
Section: Discussionmentioning
confidence: 99%